STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN BRAND AWARENESS DAGODA COFFEE - Titis Tatasari (PUTRA JAWA PUBLISHER, 2023)
As one of the brands in the coffee shop industry, Dagoda Coffee has maintained its market presence amid the competitive coffee shop industry in Jakarta. However, according to Ario, the owner of Dagoda Coffee, the marketing communication strategies implemented so far have not effectively built brand awareness for Dagoda Coffee. In this era where information is increasingly limitless, facilitating businesses to reach a broader audience, formulating marketing communication strategies to enhance brand awareness would greatly benefit Dagoda Coffee's business activities. The aim of this research is to investigate and propose effective marketing communication strategies for Dagoda Coffee in building brand awareness in the digital media realm. The research methodology employed in this study is qualitative descriptive research, encompassing interviews, observations, and data analysis. Based on the research findings, several proposed strategies are identified for Dagoda Coffee to build brand awareness in the digital media realm, considering factors such as brand exposure, customer engagement, and viral marketing.